An introduction to criminological theory / Roger Hopkins Burke. - Burke, Roger Hopkins (Routledge, 2025)
A comprehensive and up-to-date introduction to criminological theory for students taking courses in criminology at both undergraduate and postgraduate level. The text is divided into five parts, the first three addressing ideal type models of criminal behaviour the rational actor, predestined actor, and victimised actor models. The fourth part discusses integrated theories from within and across model boundaries and the final part discusses theories in the postmodern condition.